Layanan Informasi Untuk Meningkatkan Pemahaman Karir Sisawa Dalam Studi Lanjut Pada Siswa - Karo Karo, Yudha Sanada; Hendriawan, Hendriawan (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2024)
This research aims to determine the effectiveness of information services to improve students' career understanding in advanced studies for students in class XII science at SMA Negeri 1 Sungai Aur. The sample taken in this research was 58 students. This type of research is quantitative research using experimental methods, namely Pre-test Post-test Control Group Design. The data collection technique in this research used a questionnaire consisting of 37 statement items. Based on the results of analysis tests using the Wilcoxon Signed Ranks Test and the Kolmogorov Smirnov Two Independent Samples analysis test. So it can be concluded that the Asymp Sig value is less than a (0.000 0.05). So H0 is rejected and H1 is accepted. This means that there can be a significant difference regarding the career understanding of experimental group students after being given treatment in the form of information services and the control group after being given information service treatment..